IPTEKS PENGENDALIAN INTERN TERHADAP LELANG BARANG GADAI PADA PT. PEGADAIAN (PERSERO) CABANG KAROMBASAN - Lompang, Muh. Rivaldi Dg; Kalalo, Meily Y.B. (Jurnal Ipteks Akuntansi Bagi Masyarakat, 2018)
Pegadaian is one of the financial institutions owned by BUMN , where the main business is about credit something with the guarantee that the pawned tools move on the basis of financial law. This material can guarantee absolute rights to certain items of interest which are the object of guarantee of a debt and whenever it can be cashed for the payment of items that have been made in the agreement if it cannot complete the deals of payment. Auction is a sale of items for public place where the price are published in writing or directly, which increases or decreases in order to reach the highest price. The Auction is done if the customer is unable to fulfill his obligation to return or extend the mortgage item, and the Auction will be done in public place. PT. Pegadaian (Persero) has the right to sell the guarantee items belongs customers in an Auction. but before the Auction PT. Pegadaian (Persero) Karombasan Branch will confirm or remind the customer that the items in the pawn have out of date or have passed the payment limit. So the misunderstanding will not happen between the company and the customer.Keywords : procedure for auctioning goods pawned